Indonesian University students' perspectives on integrating AIEd into English language learning - Nurul Aini; Iwan Kurniarahman; Utami Widiati; Bambang Yudi Cahyono; Yazid Basthomi (Issues in educational research, 2024)
Our research investigated the integration of artificial intelligence in education (AIEd), focusing on Indonesian university students' perspectives. A quantitative survey design was based on the Technology Acceptance Model (TAM), a framework focused on perceived usefulness, modified by adding items related to affective aspects: interest, needs, excitement, and enjoyment; and cognitive aspects: listening and speaking skills with vocabulary and pronunciation components; reading skills focused on vocabulary enrichment; and writing skills with features of translation, vocabulary buildings, grammar checkers, sentence paraphrasers, idea content generators, and citation management. The questionnaire comprised 13 items based on a 4-point Likert-style scale and one item about types of AIEd. The study encompassed a cohort of 285 university students from four islands in Indonesia: Sumatra, Java, Kalimantan and Nusa Tenggara. The findings recorded 39 types of AIEd used by students. Most of the respondents have positive perceptions of the integration of AIEd, with index scores ranging from 79.1 to 84.6, while only a few of them expressed negative perceptions. Future research can consider exploring the students' perceptions through qualitative research that uses interview data.